Environment units of "Parque Estadual do Ibitipoca" southe ast of Minas Gerais State - Rodela, Luciana Graci; Tarifa, José Roberto (GEOUSP Espaço e Tempo (Online), 2001)
The Ibitipoca State Park is situated between Mantiqueira range and Andrelãndia plateau, in so u th ea st region of Minas Gerais State. It's a very im portant conservation unit. With large ecological diversity becau se contains rupestrian fields, m ountain savannah and forests, distributed in a rough terrain, rich in quartzite outcrops, and a few caves. This study is a proposal for the area individualisation in environm ental units. This individualisation was based in research and mapping of rocks, soils, relief, vegetation and w eather of the area. The results of each mapping were interconnected, individuatisating the units, resulting a map of environmental units